Središnja etapa demografske tranzicije : stanovništvo Lopuda (1870-1880) - Cvjetković, Aida (Array, 2009)
The island of Lopud owes its nineteenth-century demographic landscape to two major determinants: viewed territorially and historically, Lopud used to be part of the Dubrovnik Republic which, up to 1808, was the most developed Croatian region, and second, the island was oriented towards seafaring. All the basic demographic indicators—the number of inhabitants, natural population dynamics, mean age at marriage and the age structure by death—show that Lopud followed the overall movement of the population of the former Dubrovnik Republic, and that by the period 1870-1880, Lopud had already reached the central phase of the process of demographic transition.